Knowledge Management and Innovation: A study in the Chinese high-tech industry - Zhang, Xinfang (2011)
In the fierce competition economy environment, the Chinese high-tech companies have to maintain continuous innovation, in order to adapt to the rapid change of technology and customers’ demand. Simultaneously, the knowledge-intense era requires the companies to enhance the capability of creation and utilization knowledge. Therefore, both innovation and knowledge management (KM) bring company competitive advantages for sustaining development. In this condition, the integration of innovation and KM has become an important topic in academic studies.